FAKTOR PENDUKUNG PENGEMBANGAN OBYEK WISATA AIR TERJUN MANANGGAR DI DUSUN TAUK KECAMATAN AIR BESAR KABUPATEN LANDAK - Julianto, Agil; Zainal, Sofyan; Fahrizal, . (JURNAL HUTAN LESTARI, 2017)
Tourism is one of the most important industries to boost a country advancement. Thriving tourism has a big role in the economic, social, cultural development. Indonesian tourism industry has a growth rate of 7.2% per year which surpasses the world tourism industry by 4.7% (Legal and Public Communication of Tourism Ministry 2015). Tourist attraction is a form of activity and facility which are interrelated, and able to attract tourists to visit a particular place. Accessibility in Mananggar Waterfall tourist attraction is not certain whether it affects the level of tourist visit, so further assessment is needed which aims to determine the supporting factors, development, perception regarding the Mananggar Waterfall tourist attraction. This research was conducted at Nyiut Mountain nature reserve. This research showed the highest score of the element and sub elements that have been rated regarded elements of variation of activities showing the highest score of 29.84% with percentage of 15.29%. While the lowest scores of elements and sub elements of location cleanliness of 17.9% with percentage of 12.42%. Research findings showed that the overall elements and sub elements were rated equal to 156.04. The results can be multiplied with weight of the scores for Mananggar Waterfall with overall score of 156.04 x 6 = 936.24. The Mananggar Waterfall has an areal attraction score of medium (B) to be developed as a nature tourist attraction. Keywords: Mananggar waterfall, natural tourist, object natural attactions